Quality of Life among Hemodialysis Patients with or Without Diabetes Mellitus at Undata Hospital, Palu: Kualitas Hidup Pasien Yang Menjalani Hemodialisa Dengan Komplikasi dan Tanpa Komplikasi Diabetes Melitus Di RSUD Undata Palu - Diana, Khusnul; Kristiono, Oviani; Tandah, Muhamad Rinaldhi (Universitas Tadulako, 2025)
Background: Hemodialysis is a renal replacement therapy for patients with end-stage chronic kidney disease (CKD). Diabetes mellitus is a leading cause of CKD. Hemodialysis can affect health-related quality of life (HRQoL), as biological and psychological domains and daily life may vary by age, sex, education, and type of treatment received by patients.Objectives: To assess HRQoL among hemodialysis patients at Undata Hospital, Palu, according to age, sex, comorbidities, years of undergoing dialysis, and education level.Methods: An observational study was conducted using convenience sampling. Data were collected through structured questionnaires and medical records. The study included a total of 88 participants who met the inclusion and exclusion criteria. Instruments used included demographic characteristics, social functioning, mental and physical well-being, and overall quality of life descriptions.Results: Most participants were male (55.7%), aged 31–56 years (68.2%), and undergoing HD twice weekly (93.2%). The HRQoL domains were moderate. Forty patients (45.5%) had no diabetes and 48 had diabetes mellitus. Mean HRQoL scores were 46.60 for patients without DM and 45.91 for patients with DM. There was no significant difference in HRQoL based on age (p=0.104), dialysis duration (p=0.015), or educational background (p=0.973). Only comorbidity was associated (p=0.750).Conclusion: Hemodialysis patients with diabetes mellitus experience lower HRQoL than those without. Age, dialysis duration, and education level are additional determinants of HRQoL in this population.